The Importance of Complementarity in the Territorial Cohesion and Sustainability of Rural Areas: The Case of Cambres, a Douro Winegrowing Area, and Magueija, a Mountainous Area - Pina, Helena (Journal for Geography, 2010)
Although the rural world reveals several troubling trends, such as demographic decline and stagnation/deterioration of the economic framework, there are multiple potentialities requiring urgent vitalization. Furthermore, heterogeneity predominates, a fact that becomes very clear when comparing the territorial setting of Cambres, a parish located in the Lamego municipality, part of the Douro winegrowing area and the area classified as World Heritage by UNESCO, with another parish set within mountainous terrain, Magueija, also located in the Lamego municipality, whose endogenous potential is completely neglected. As such, many challenges compromise its development and conformance with one of the main strategic vectors for the region, which is territorial cohesion.